2021
DOI: 10.1080/14616696.2020.1869283
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the coronavirus crisis on European societies. What have we learnt and where do we go from here? – Introduction to the COVID volume

Abstract: The coronavirus pandemic, which first impacted European societies in early 2020, has created a twofold crisis by combining a health threat with economic turmoil. While the crisis has affected all European societies very significantly, its impact varies across countries, social groups, and societal domains. In an effort to provide a first overview of the effect of the coronavirus crisis, in this editorial we discuss contributions of 58 papers published as part of this special issue. These early research papers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 65 publications
2
57
0
1
Order By: Relevance
“…These COVID-19 induced lockdowns have led to serious concerns regarding students' academic progress and their well-being. At the same time, the COVID-19 pandemic can exacerbate existing patterns of social inequalities in education ( Grasso et al, 2021 , p. 7). Initial studies of the effects of the spring 2020 lockdown in the Netherlands demonstrated that the learning loss due to closed schools is more pronounced among students of lower socioeconomic status (SES) ( Engzell et al, 2021 ; Nationaal Cohort Onderzoek Onderwijs, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These COVID-19 induced lockdowns have led to serious concerns regarding students' academic progress and their well-being. At the same time, the COVID-19 pandemic can exacerbate existing patterns of social inequalities in education ( Grasso et al, 2021 , p. 7). Initial studies of the effects of the spring 2020 lockdown in the Netherlands demonstrated that the learning loss due to closed schools is more pronounced among students of lower socioeconomic status (SES) ( Engzell et al, 2021 ; Nationaal Cohort Onderzoek Onderwijs, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 complicated refugee integration in Germany due to concerns about health and financial risk [31]. The pandemic increased the feeling of uncertainty in refugees' everyday working life and diminished the mechanism and objectives to improve their working conditions [25].…”
Section: Literature Review: Covid-19 Effect On Refugee Integrationmentioning
confidence: 99%
“…However, the empirical evidence on the pandemic's effect on gender inequalities thus far is mixed (Grasso et al 2021). Some survey studies have found that women were more likely than men to reduce their working hours or stop working after the start of the nationwide lockdowns (e.g., Collins et al 2020;Farré et al 2020; for the United States, Spain, and Germany).…”
Section: Introductionmentioning
confidence: 99%